DIGITALIZATION OF PROCESSES IN SMALL SERVICE BUSINESSES - Savchenko, Yaroslav (Global Prosperity, 2025)
Abstract. The article focuses on analyzing the digital transformation of processes in small service businesses in the United States within the context of the digital economy of 2025. The aim of the study is to examine the current state, key challenges, level of digitalization, and strategic directions for the development of small service enterprises in the U.S. in the context of the 2025 digital economy. The study employed general scientific methods of cognition, such as analysis and synthesis, induction and deduction, systematization, generalization, comparison, along with elements of structural-functional and forecasting approaches. The findings reveal that as of 2025, small service businesses in the U.S. demonstrate stable growth and make a significant contribution to the national economy. Out of over 34.8 million small enterprises, the majority operate in the service sector, particularly in retail (15%), food services (13%), and the beauty and fitness industries (10%). These businesses provide employment to nearly half of the country’s working-age population, with over one-third being family-owned companies. At the same time, a number of critical issues were identified: limited access to funding (40% of businesses are unable to invest in digitalization), financial instability, weak internal customer service infrastructure, a shortage of skilled labor, and a lack of long-term digital planning. The most vulnerable category remains microbusinesses with fewer than 10 employees, accounting for over 90% of the sector. The study also examines the level of digitalization, which is generally high at the basic level – 95% of businesses use at least one digital platform. However, only 15% of microbusinesses can be classified as early technology adopters, while more than half of respondents believe digital solutions are financially out of reach. In 2025, a decline in the adoption of new digital tools was recorded due to inflation, rising IT infrastructure costs, and regulatory uncertainty. The practical value of the research lies in identifying strategic approaches to improving the digital maturity of small businesses, taking into account current barriers and opportunities.